Study of the antimicrobial preservatives effectiveness test in development of the combined syrup composition - Шмалько, Олександр Олександрович; Вишневська, Лілія Іванівна; Стрілець, Оксана Петрівна; Яковенко, Володимир Костянтинович (ScienceRise: Pharmaceutical Science, 2016)
Aim. The aim of our research was to substantiate and to study the antimicrobial preservatives effectiveness in development of the combined syrup basis composition based on the natural extracts and applied for the hepatobiliary system and gallbladder disorders treatment. Methods. Biological pharmacopoeial method (antimicrobial preservatives effectiveness) was used. Results. According to the results of research of the antimicrobial preservatives series, following data were obtained. № 1 and № 2 syrup series (containing Nipagin : Nipasol (3 : 1) 0.1 % and 0.2 %), № 3 and № 4 series (containing Potassium sorbate 0.1% and 0.2%), №5 and №6 series (containing Sodium benzoate 0.1 % and 0.2 %) met the criteria of antimicrobial preservatives effectiveness evaluation recommended by the SPhU for oral drugs. It has been found, that all experimental samples of the developed syrups after adding the selected preservatives are promising for the further research in area of oral remedies creation. Nevertheless, the antimicrobial effectiveness of Potassium sorbate is slightly higher (lg of reducing the number for Candida albicans АТСС 885-653 viable cells is 3.55; for Aspergillus brasiliensis АТСС 16404 is 2,3), and antimicrobial activity spectrum is wider, which will promote the quality of the developed syrup, as well as during its storage period. Therefore, Potassium sorbate will be used as a preservative in the following research. Results. The advisability of using of Potassium sorbate as a preservative in development of the combined syrup basis with complex pharmacological activity was theoretically substantiated and experimentally proved